Microstructural and microvascular features of white matter hyperintensities and their association with small vessel disease markers - Lily L. Wang; Brady J. Williamson; Bin Zhang; Aakanksha Sriwastawa; Yasmin N. Aziz; Eleni Antzoulatos; Cody B. Stephens; Achala Vagal; Pooja Khatri; Mark W. DiFrancesco (Scientific Reports)
Abstract White matter hyperintensities (WMH) are the most prominent imaging feature of small vessel disease (SVD). WMH and other imaging features of SVD are likely the result of ongoing insults associated with cognitive decline and cerebrovascular events. Emerging evidence suggests degradation of the neurovascular unit may underlie the pathogenesis of SVD. This prospective pilot study employed MRI in 19 subjects (68.2 ± 11.5 years of age) for diffusion-weighted imaging, applied to intravoxel incoherent motion (IVIM) modeling, to characterize microstructural and microvascular properties throughout the brain and arterial spin labeling, using multiple labeling and delay times, to measure dynamic perfusion properties including blood–brain barrier permeability (PS) in gray matter (GM). IVIM revealed WMH to have significantly greater blood volume fraction and lower pseudodiffusion and bulk diffusion than normal-appearing white matter (NAWM). IVIM parameters and PS, in canonical GM network regions, correlated with WMH volume with at least moderate effect size. Findings suggest the potential for neovascularization and evidence of restricted diffusion in WMH compared to surrounding NAWM. Regional changes in GM pertaining to the NVU scale in proportion to WMH load. Observed GM changes precede visible MR imaging abnormalities. Their early detection could elucidate SVD mechanisms of brain injury and inform future preventative measures.